The Effect of Female Labor Force Participation Rate, Average Years of Schooling for Women, and Gender Inequality Index on Economic Growth in Indonesia: Panel Data Analysis 2018-2024 - Putri Permata Liza; Ambya Ambya (International Journal of Economics and Management Sciences, 2026)
This research examines the impact of the Female Labor Force Participation Rate (FLFPR), women’s average years of schooling, and the Gender Inequality Index on economic growth in Indonesia during 2018-2024, with investment included as a control variable. The study uses a quantitative explanatory method and applies panel data regression analysis covering 13 provinces in Indonesia. To identify the most suitable estimation model, the Chow test, Husman test, and Lagrange Multipilier test were performed, and the Fixed Effect Model (FEM) was ultimately chosen.  The findings reveal that FLFPR and investment significantly contribute to economic growth in a positive direction. In contrast, women’s average years of schooling shows a positive relationship but does not significantly influence economic growth. Meanwhile, the Gender Inequality Index is found to have a significant negative relationship with economic growth. Overall, the results imply that stronger female participation in the workforce and lower levels of gender inequality can support higher economic growth in Indonesia.